Assessment of biological age with conventional ultrasound imaging as an alternative to x-ray—A pilot study in youth soccer - Widmer, C.; Busch, J. D.; Born, D.-P.; Romann, M. (European Journal of Sport Science, 2025)
The aim of the study was to evaluate conventional ultrasound (US) as a radiation-free alternative to X-ray for determining biological age (BA; indicated by skeletal age). BA, was determined in 24 healthy, male, elite youth soccer goalkeepers around peak height velocity (11-16 years of age) using both X-ray and conventional US scans of the left hand. X-ray scans were evaluated using the Tanner-Whitehouse 2 method. Conventional US scans served to determine BA via ossification ratios of 13 hand and wrist bones. The new conventional US method showed very strong correlation with X-ray r = 0.90 (p < 0.05). However, the agreement for the difference in BA and CA, which accounts for age-related variance, was classified poor (ICC = 0.48, p < 0.05). Additionally, linear regression analysis and the Bland-Altman plot suggested the presence of a systematic and proportional overestimation of BA in younger players and an underestimation of BA in older players. Furthermore, Cohen's kappa showed a moderate agreement between players' classification into maturity groups for the two assessment methods. In conclusion, our study has shown that using US-derived ossification ratios did not deliver valid results compared to X-ray when determining BA in youth soccer goalkeepers.